Economic conditions, education, and parity-specific fertility: A sub-national regional study across 15 countries in Europe - Nisén, Jessica; Klüsener, Sebastian; Dahlberg, Johan; Dommermuth, Lars; Jasilioniene, Aiva; Kreyenfeld, Michaela; Lappegård, Trude; Li, Peng; Martikainen, Pekka; Neels, Karel; Riederer, Bernhard; te Riele, Saskia; et al. (John Wiley & Sons Ltd, 2025)
There is a longstanding interest in the link between economic conditions and fertility levels. Most research measuring economic development has focused on national-level patterns and period total fertility levels. We aim to extend existing knowledge by carrying out a sub-national regional analysis of the link between economic conditions and parity-specific cohort fertility, while taking into account heterogeneity by educational level. We study three fertility outcomes by women’s education: the share of women who remain childless, the mean number of children per mother, and the mean number of children per woman. For this analysis we harmonized register, census, and large-scale survey data from 15 European countries, with a focus on women born in the late 1960s. Women’s fertility was measured at the end of their reproductive careers and combined with contextual information, including information on the regional GDP (per capita). In our multiple regression models that controlled for country-level factors, we found that GDP was positively associated with childlessness among women with medium and high levels of education. However, GDP was negatively associated with the number of children per mother among women with low levels of education. These findings show that the relationship between economic conditions and fertility varies depending on the level of education of the women, and it differs between childlessness and continued childbearing. High-income contexts may be less supportive of continued childbearing for women with lower levels of education.